Effects of energy level in finisher diets and slaughter age of on the performance and carcass yield in broiler chickens - Albuquerque, R de; Faria, DE de; Junqueira, Otto Mack [UNESP]; Salvador, D; Faria Filho, DE de [UNESP]; Rizzo, MF (Fundação APINCO de Ciência e Tecnologia Avícolas, 2003)
Male broilers were used to evaluate the effects of different energy levels in finisher diets and age of slaughter on performance, production pattern and carcass yield. Experimental design was a 2x3 factorial arrangement: energy level (ME) in the finisher diet (3,200 and 3,600 kcal ME/kg) and age of slaughter (42, 49 and 56 days), resulting in six treatments with four replicates. The finisher diet was fed only in the last week of the growing period. Characteristics evaluated were feed consumption (FC), body weight gain (WG), feed conversion (FC), energy intake (EI), caloric conversion (CC), efficiency production index, production pattern, and carcass yield. The results showed better WG and CC for broilers fed 3,200 kcal ME/kg finisher diet. Broilers slaughtered at 42 and 49 days of age had better performance and higher annual production than broilers slaughtered at 56 days of age. Carcass yield was influenced by slaughter age and better breast yield was seen at 49 and 56 days than at 42 days of age. It was concluded that 3,200 kcal ME/kg induced the best overall performance. Poultry houses were efficiently used when broilers were slaughtered at 42 days of age. Meat:bone ratio was improved for broilers slaughtered at 49 and 56 days of age.
Keywords: Broilers; Carcass yield; Energy levels; feeding program; finisher diet